Premorbid, cardioselective beta-blocker exposure decreases ICU mortality in septic patients defined by sepsis-3. (25th November 2020) - Kuo, M; Chou, R.H; Wu, C.H; Huang, P.H; Lin, S.J
Abstract: Introduction: Beta-blockers may exert a protective effect against the catecholaminergic myocardial injury in septic patients. The difference between cardioselective and non-selective beta blockers was not fully elaborated. The aim of this study was to investigate the association between premorbid prescriptions of different class of beta-blockers and mortality rate in septic patients. Methods: We retrospectively screened 2678 patients admitted to the ICU during December 2015 to July 2017. Premorbid beta-blocker exposure was defined as prescription of any beta blocker for at least 1 month. Bisoprolol, esmolol, and atenolol were classified as cardioselective beta-blockers, and others were classified as non-selective beta-blockers. Results: Among 1262 septic patients, 209 (16.6%) cases were long-term beta-blockers users. Patients with premorbid beta-blocker exposure were associated with higher BP, lower HR, lactate concentration, and improved ICU mortality. However, only premorbid cardioselective beta-blocker users (adjusted HR 0.26; 95% CI 0.11–0.64; p=0.003), but not non-selective beta-blocker users (adjusted HR 0.66; 95% CI 0.29–1.51; p=0.326), were associated with reduced ICU mortality. Conclusion: Only premorbid cardioselective beta-blockers, but not non-selective beta-blockers, were associated with improved mortality in septic patients. These findings supported the cardioprotective effect and clinical benefits of beta-blocker in septic patients. Funding Acknowledgement: Type of funding source: None